PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RESTORAN INDUS UBUD GIANYAR - Arie Sulistyawati, Ni Made; Seminari, Ni Ketut (E-Jurnal Manajemen, 2015)
Quality of service is an important factor and roots that are able to provide satisfaction for its customers. So that customers are satisfied with the services provided. The purpose of this study was to determine the effect of service quality on customer satisfaction. This study uses primary data sourced from direct observation and questionnaires were distributed to the respondents who subsequently analyzed using linear analysis berganda.Hasil data analysis found that the variable physical evidence, reliability, responsiveness, assurance, empathy, and gender differences affect the customer satisfaction at Restaurant Indus Ubud.
Keywords: Quality of Service, Customer Satisfaction, Gender Differences